Optimization of the operative conditions for heteropolyacids synthesis through ion exchange - Matkovic, Silvana R. (2005)
Phospho-tungstic and phospho-molybdic Wells-Dawson heteropolyacids, H6P2W18O62.xH2O and H6P2Mo18O62.xH2O respectively, were synthesized through ion exchange with a higher yield (∼ 90%) than the conventional organic route (∼ 70%). Pure, non-degraded heteropolyacids are obtained when the corresponding ammonium salt [(NH4) 6P2W18O62.13H2O or (NH4)6P2Mo18O62.12H2O] is kept in contact with an acid resin [about (1:0.8) salt:resin weight ratio] up to three days. The use of an organic media instead of an aqueous media greatly favors the completeness of the exchange.